Hereditary spherocytosis: a risk factor for thigh pressure myonecrosis in posterior spine surgery. Issue 6 (November 2020) - Marasigan, Joanne Abby M.; Solano, Mitchell A.; Wicklund, Brian M.; Schwend, Richard M.
Abstract : The objective of this study was to make surgeons aware of a potential pressure complication in posterior spine surgery for patients with hereditary spherocytosis (HS) and to present a plausible hypothesis for injury. Posterior spine surgery is common practice for adolescent idiopathic scoliosis (AIS). Common, less severe surgical risks include pressure ulcers; while rare, more severe pressure complications include rhabdomyolysis and compartment syndrome. In patients with HS, a familial hemolytic disorder with altered red cell deformability, it is unknown if their red cell disorder is an additional risk factor for pressure-related surgical injuries. Two patients with HS, an 18-year-old male and a 17-year-old female, were both post-splenectomy and underwent revision posterior spinal fusion and instrumentation for progressive AIS. Surgery lasted 9 hours and 7 hours respectively, with no intraoperative complications other than prolonged surgical time due to revision nature of the deformities. Thigh redness and swelling was noted in both patients directly deep to the thigh pads. Thigh myonecrosis was diagnosed with eventual recovery in both cases. Patients with HS may be at inherent more risk of pressure complications during posterior spine surgery. We propose that thigh myonecrosis occurs with decreased perfusion and hemolysis from HS erythrocytes' inherent fragility, decreased deformability within capillaries, and prolonged microvasculature compression from positioning, causing poor microvascular perfusion, tissue ischemia, and reperfusion injury. Level of veidence: IV.